Morphogenesis of Cerebellum in Buffalo Foetus - R.D, Srinath (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on brains of 18 buffalo foetuses. At 7.4 cm curved crown rump length CVRL, cerebellum appeared as medially expanded bilateral dorsal grooves, whereas at 18.2 cm CVRL a small midline portion formed vermis and two lateral portions forming cerebellar hemispheres were observed. At 70 cm CVRL, the rostral lobe was divided into lingulae, central lobule and culmen. At 90 cm CVRL, all the nine classical lobules of cerebellum were distinguished and at 110 cm CVRL, the cerebellum acquired all the characteristics of adult buffalo. Histogenesis of cerebellum showed that it was expanded dorsally as a dumbbell shaped structureat 62 days of gestation. The developing cerebellum was divided into anterior and posterior parts by a transverse fissure. It was observed that the anterior part of cerebellum developed faster than the posterior one. During initial stages of development, the cerebellar plate consisted of neuroepithelial, intermediate and marginal layer. A superficial layer of proliferating neuroepithelial cells appeared as external granular layer (EGL). Formation of EGL was an unique feature in developing cerebellum which disappeared later on. The formation of primitive Purkinje cells was noticed in 122 days as Purkinje cell bodies. With the formation of primitive Purkinje cell layer at 137 days, migrating cells from EGL started to aggregate beneath this layer to form internal granular layer. The present study correlated the chronological pattern of age related histogenesis and developmental anatomy ofcerebellum in buffalo foetus.